Lactobacillus crispatus Strain KT-11 S-Layer Protein Inhibits Rotavirus Infection - Kawahara, Takeshi; Shimizu, Issei; Tanaka, Yuuki; Tobita, Keisuke; Tomokiyo, Mikado; Watanabe, Itsuki (Frontiers in Microbiology, 2022)
S-layer proteins (SLPs), which are present in the external layer of certain strains of lactic acid bacteria isolated from the intestinal tract, are known to recognize and bind to specific proteins and glycan structures and contribute to adsorption to the host intestinal mucosa. The binding properties of certain SLPs are considered to exert a competitive inhibitory effect on infection because similar properties are involved in the infection mechanisms of several viruses. However, little is known regarding whether SLPs directly inhibit viral infection. In the present study, we investigated the effect of an SLP of the Lactobacillus crispatus KT-11 strain, a probiotic strain isolated from a healthy human infant, on human rotavirus infection. The impact of lithium chloride extract (LE) of KT-11, which contains SLP, on the infection of the P[4] genotype human rotavirus strain DS-1 was evaluated by monitoring the amplification of viral protein 6 (VP6) expression in human intestinal epithelial Caco-2 cells by quantitative reverse transcription-polymerase chain reaction assay after infection. KT-11 LE showed a significant suppressive effect on DS-1 infection in a dose-dependent manner with pre-infection treatment, whereas post-infection treatment was not effective. A 45 KDa protein isolated from KT-11 LE was investigated for homology using the BLAST database and was found to be a novel SLP. KT-11 SLP significantly inhibited the proliferative process of the DS-1 strain but not that of the P[8] genotype human rotavirus strain Wa. KT-11 SLP exerted significant inhibitory effect on DS-1 infection by pre-infection treatment even after digestion with gastric juice up to 2 h. Our results provided crucial evidence that SLPs from certain Lactobacillus strains can inhibit human rotavirus infection of intestinal epithelial cells.